AWARENESS ABOUT WEGENERS GRANULOMATOSIS DISEASE AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Wegener’s granulomatosis (WG) is a systemic disease characterized by necrotizing granulomatous inflammation of the upper and lower respiratory tract, glomerulonephritis, and vasculitis The clinical manifestations and laboratory findings suggest an autoimmune disease resulting from a hypersensitivity reaction to some environmental agent .The purpose of the survey is to assess the awareness about wegeners granulomatosis disease amongst dental students. A cross-sectional survey was done with a questionnaire comprising a total of ten multiple-choice questions, which were distributed to 100 undergraduate dental students. The questions elicited awareness about the etiology, clinical features, diagnostic tests, treatment methods and complications of wegeners granulomatosis. The responses were collected and analysed.7% were aware of etiology of Wegeners granulomatosis, 9% were aware of clinical features of Wegeners granulomatosis, 5% were aware of diagnostic tests of Wegeners granulomatosis, 5% were aware of treatment of Wegeners granulomatosis, and 4% were aware of complications of Wegeners granulomatosis. The awareness about Wegener’s granulomatosis among dental students is inadequate.Granulomatosis of Wegener is a relatively uncommon, autoimmune condition of unknown origin. Without medication, thus many patients would then inevitably die of those same illness. Therefore, awareness and education initiatives must be pursued to enlighten students about this illness.